Management of hypoglycemia in newborn: Turkish Neonatal and Pediatric Endocrinology and Diabetes Societies consensus report - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Hypoglycemia is one of the most important and most common metabolic problems of the newborn because it poses a risk of neurological injury, if it is prolonged and recurs. Therefore, newborns who carry a risk of hypoglycemia should be fed immediately after delivery and the blood glucose level should be measured with intervals of 2-3 hours from the 30th minute alter feeding. The threshold value for hypoglycemia is 40 mg/dL for the first 24 hours in symptomatic babies. In asymptomatic babies, this value is considered 25 mg/dL for 0-4 hours, 35 mg/dl for 4-24 hours, 50 mg/dL alter 24 hours and 60 mg/dL after 48 hours. Screening should be performed with bed-side test sticks. When values near the limit value are obtained, confirmation with laboratory method should be done and treatment should be initiated, if necessary. The level targeted with treatment is considered 50 mg/dL in the postnatal first 48 hours before feeding, 60 mg/dL after 48 hours in babies with high risk and above 70 mg/dL in babies with permanent hypoglycemia. In cases in which the blood glucose level is below the threshold value and can not be increased by feeding, a glucose infusion of 6-8 mg/kg/min should be initiated. If symptoms accompany, a mini bolus of 10% dextrose (2 ml/kg/min) should accompany. Incements (2 mg/kg/min) should be performed, if the target level can not be achieved and decrements (2 ml/kg/min) should be performed, if nutrition and stabilization is provided. The infusion should be discontinued, if the infusion rate decreases to 3-5 mg/kg/min. If necessary, blood samples should be obtained during hypoglycemia in terms of differential diagnosis and the investigation should be performed following a 6-hour fasting period in babies fed enterally and at any time when the plasma glucose is <50 mg/dL in babies receiving parenteral infusion. The hypoglycemic babies in the risk group whose infusions have been terminated can be discharged, if the plasma glucose level is found to be at the target level for two times before feeding and babies with permanent, severe or resistant hypoglycemia can be discharged, if the plasma glucose level is >60 mg/dL following a 6-hour fast.
Keywords: Glucose; hypoglycemia; infusion; newborn; NEURODEVELOPMENTAL OUTCOMES; GESTATIONAL-AGE; BRAIN-INJURY; LATE-PRETERM; INFANTS; DEFINITION; FEATURES; BABIES; RISK